Legal analysis for exploring and utilizing continental shelf resources: A comparative Study between Saudi maritime zones law and international law of the Sea - Abobaker, Mohammed Yahya (International Journal of Innovative Research and Scientific Studies, 2025)
The continental shelf (CS) is a fundamental aspect of maritime sovereignty, granting coastal states exclusive rights over its natural resources under both national and international law. This study aims to analyze the role of the Saudi Maritime Zones Law (SMLZ) in strengthening the Kingdom’s sovereignty over its CS by comparing its provisions with those of the United Nations Convention on the Law of the Sea (UNCLOS), particularly Articles 77, 78, and 81. The study employs a comparative legal analysis between Saudi national legislation and UNCLOS provisions, focusing on Articles 18, 19, 20, and 21 of SMLZ. The study indicates that SMLZ enhances the Kingdom’s national sovereignty by providing a precise and independent legal framework, granting the Kingdom broad powers to regulate maritime activities and exploit CS resources while safeguarding its national interests and international commitments. The study recommends an urgent need to update and develop both international and domestic maritime laws to ensure effective management of marine resources, enhance national sovereignty, provide clearer legal mechanisms for dispute resolution, and ensure the sustainability of these resources for future generations.